Measuring bank efficiency: Tradition or sophistication? - A note - Jenifer Daley; Kent Matthews (Cardiff University, Cardiff Business School, 2009)
The recent literature on measuring bank performance indicates a preference for sophisticated techniques over simple accounting ratios. We explore the results and relationships between bank efficiency estimates using accounting ratios and Data Envelope Analysis (DEA) with bootstrap among Jamaican banks between 1998 and 2007. The results indicate different outcomes for the traditional accounting ratios and the sophisticated DEA methodology in the measurement of bank efficiency. GLS random effects two-variable regression tests for superiority using a risk index for insolvency suggest an advantage in favour of the DEA.
Keywords: G21; G28; G29; 330; Bank efficiency; Jamaica; Accounting Ratios; Bank; Bankgeschäft; Unternehmenserfolg; Messung; Jamaika